Belize : Technical Assistance Report-Public Investment Management Assessment. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2020)
The level of public investment in Belize has varied over the past years in the context of existing constraints. The sharp increase in public debt has limited available fiscal space.1 This has resulted in an increase in externally financed investments as a share of the capital budget and a growing interest in public private partnerships (PPPs) to help achieve the government of Belize's national strategy objectives.2 However, the correlation between Belize's public investment and GDP growth remains weak, and the public capital stock as a ratio to GDP shows a sharp deterioration, possibly pointing to investment inefficiencies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet